(untitled) (Baghdad Science Journal, 2019)
The impact of a Schiff base namely 2-((thiophen-2-ylmethylene)amino)benzenethiol to corrode mild steel in 1 M HCl resolved was evaluated using different weight loss technique and scanning electron microscopy (SEM).different weight measurements to expand that the 2-((thiophen-2-ylmethylene) amino) benzenethiol inhibits the corrosion of mild steel through adsorbing of top for mild steel and block the active locality. The inhibitive impacts of 2-((thiophen-2-ylmethylene)amino)benzenethiol increase with increasing concentration and decrease with increasing temperature. SEM to checking revealed that the alloy surface was quite unaffected and formed protective film on its surface. The investigated inhibitor become as a shield for the mild steel surface from corrosive solution. Quantum chemical investigations corroborate experimental results well. The synthesized inhibitor was characterized employing NMR (nuclear magnetic resonance), FT-IR (Fourier-transform infrared) spectroscopies and CHN elemental analysis.